The family Epicriidae in Slovakia: annotated faunal synopsis and description of a new species of Epicrius (Acari, Mesostigmata, Epicriidae) - Mašán, Peter (Zootaxa, 2008)
Eight species of the family Epicriidae, all in the genus Epicrius Canestrini & Fanzago, 1877, are documented from Slovakia: E. bureschi Balogh, 1958, E. mollis (Kramer, 1876), E. monticola Bregetova, 1977, E. resinae Karg, 1971, E. schusteri Błaszak & Alberti, 1989, E. simoni sp. nov., E. sophiae Bregetova, 1977, and E. tauricus Bregetova, 1977. A new species is here described (E. simoni sp. nov.), and one other species is redescribed and illustrated for the first time (E. sophiae). Epicrius kargi Solomon, 1978 is synonymised with E. tauricus. Two of the species are recorded from Slovakia for the first time (E. schusteri and E. sophiae), and one has been wrongly recorded from Slovakia (E. stellatus Balogh, 1958). Information on ecology and regional distribution is provided for the most common and abundant species, E. monticola, E. resinae, E. schusteri, and E. tauricus. A key to the Slovakian species of Epicrius is also provided.